This article will examine circles that are mutually tangent to each other with distinct points of tangency. We build up from two, to three, then to four mutually tangent circles. This will prepare the way for the next article on Descartes' Circle Theorem.
Let R denote the set of real numbers, R+ the non-negative real numbers, RxR = R2 = {X=(x,y): x∈ R,y ∈R} the real plane. That is R2 is the set of all ordered pairs of real numbers.
A relation in R2 is any subset of R2. Thus a line, {X:y=ax+b}, and a circle, {X: XA=r}, are relations in R2, the latter having radius r and center A.
Two circles are tangent to each other (mutually tangent) if the relations defining them have exactly one point in common.
Two Tangent Circles
Given circle EA = {X:XA = rA}, find circle EC = {X:XC = rC} tangent to EA. There are two cases. Case A: EA surrounds EC ; Case B: EA and EC are externally tangent to each other.
- Case A: Let C ∈ {X: XA < rA}, i.e. C is in the interior of EA. Then EC = {X: XC = rA-AC} is tangent to EA. Proof: First we show they have a point in common. Let the radial segment from A through C hit EA at P. Then P ∈ EA and rA =AP=AC+CP. So CP=rA-AC and P ∈ EC. Now we show P is unique. Suppose there is another point Q ≠ P such that Q ∈ EA and EC. Then AQP form a triangle. AQ = rA and CQ = rA - AC. Thus CQ = AQ-AC. But in triangle ΔACQ we must have CQ + AC > AQ. Thus there is no such Q. That is P is the unique intersection of the two circles. Note: In particular, the line joining the centers A and C includes the point of tangency, P.
- Case B: Let C ∈ {X: XA > rA}, i.e. C is in the exterior of EA. Then EC = {X: XC = AC-rA} is tangent to EA. Proof: Similar to case A. Draw the segment AC and let it intersect EA at P. Then PC=AC-rA, so P is also in EA. Again suppose there is another point Q ≠ P such that Q ∈ EA and EC. If Q is collinear with A,P, and C then QC = rA + AC so Q ∉ EC. In ΔAQC, AQ + QC > AC so QC > AC - AQ = AC - rA, so Q ∉ EC. Thus P is the unique point of intersection of the two circles so they are mutually tangent.
Three Mutually Tangent Circles with Three Distinct Points of Tangency
For each of the cases of two tangent circles we now look at how to include a third circle which is mutually tangent to the two at three distinct points of tangency. In Case A, in order for the points of tangency to be distinct, the new circle EB must be surrounded by EA. In Case B, EB might surround EA and EC or it might be externally tangent, to both of them.
- Case A: We can find the third tangent circle in two ways. Case A1: Choose any point B ∈ {X:XA < rA} ∩ {X:XC > rC} as the center of EB and then find rB. Case A2: Choose any 0 < rB < rA-rC, the range of possible radius measurements for circles with centers inside EA and outside EC, and then find the center B.
- Case B: We have two cases and each can be done in two ways (as with Case A). Case B1: EB surrounds EA and EC. Case B2: EA, EB, and EC are externally tangent to one another. We divide these into four cases. Case B11: Choose B in the exterior of both EA and EC then find rB. Case B12: Choose a radius 0 < rB and find a center B. Case B21: Choose B in the exterior of both EA and EC then find rB. Case B22: Choose a radius 0 < rB and find a center B.
First we examine cases A1, B11, and B21 where we are given A, rA, C, rC and B and we need to find rB. Note, we will also get expressions for rA and rC which will be useful throughout. In each case we consider ΔABC with sides of length a=BC, b=AC, and c=AB and semi-perimeter s = (a + b + c)/2.
-
Case B11: We can write rB = c + rA = a + rC and b = rA + rC. Thus a+ B + c = 2s = 2rB. Thus
- rB = s
- rA = s-c
- rC = s-a.
-
Case B21: Using the fact that the segment joining the centers of two tangent circles includes the point of tangency (from the analysis of two tangent circles), we have a = rB + rC, b = rA + rC, and c = rA + rB. Thus (a + b + c) = 2s = 2(rA + rB + rC). Therefore,
- rB = s - (rA + rC) = s-b
- rA = s-a
- rC = s-c.
- Here is a picture of the two constructions using A(0,0), C(3,0) and B(1,1). The black trio is case B11 and the orange trio is case B21.
- Case A1: Choose B in the interior of EA and the exterior of EC. From Case B11 above we know that rB = s-c.
Next we will look at the cases A2, B21, and B22 where we are given A, rA, C, rC and rB and we need to find B. In each case we will set up a system of two quadratic equations parameterized with a linear function of rB which we can solve for B.
- Case A2: B must satisfy BA = rA - rB and BC = rB + rC. Notice that EB is at its maximum radius when B is collinear with A and C. In this case 2rB + 2rC = 2rA. Thus the maximum value for rB is rA - rC.
- Case B12: EB surrounds. B must satisfy BA = rA - rB and BC = rB - rC.
- Case B22: EA, EB, EC externally tangent. B must satisfy BA = rA + rB and BC = rB + rC.
Since A and C are arbitrary, we assume A is the origin of a rectilinear coordinate system, so A = (0,0). Also without loss of generality we can take C = (b,0) so that AC = b in ΔABC. Then our system, in general, becomes
- x2 + y2 = ƒ12(rB)
- (x-b)2 + y2 = ƒ22(rB)
Solve in terms of parameter rB by subtracting the second equation from the first to get 2bx - b2 = ƒ12 - ƒ22 or,
x = (b2 + ƒ12 - ƒ22)/2b and y = ±√[ƒ12 - x2]. We get the solutions for our three cases by specifying b, ƒ1 and ƒ1for each.
- Case A2: b = (rA - rC); ƒ1(rB) = rA - rB; ƒ2(rB) = rC + rB, 0 < rB < rA - rC. Case B12: b = (rA - rC); ƒ1(rB) = rA - rB; ƒ2(rB) = rB - rC.
- Case B22: b = (rA - rC); ƒ1(rB) = rA + rB; ƒ2(rB) = rC + rB.
In each case we get two solutions for B, one above the line through A and C and one below. We must have rA ≠ rB to get a solution for B.
Four Mutually Tangent Circles with Six Distinct Points of Tangency
From the last section, we have two distinct cases of three mutually tangent circles with distinct points of tangency to extend to a fourth circle. Case A: One of the three surrounds the other two. Case B: the three circles are externally tangent to each other. In these cases, to add a 4th tangent circle, we will get systems of three quadratic equations in three unknowns, the coordinates of the center D and the radius d of the fourth tangent circle ED. As in the case of three circles, the difference in the systems are the linear functions of d in those systems. We will call A = (0,0), C(b1,0), and B(c1,c2). The sides of ΔABC are then a = √[(c1-b1)2 + c22], b = b1, and c = √[c12 + c22]. Again let s = (a + b + c)/2.
-
Case A:
In this case EA surrounds the other three circles and there are two placements for ED; one on the same side of the line through B and C as A and one on the far side of this line from A.
- AD = ƒ1(d) = rA - d
- BD = ƒ2(d) = rB + d
- CD = ƒ3(d) = rC + d
-
Case B:
In the case that ED surrounds EA, EB, and EC, then AD = ƒ1(d) = d - rA; BD = ƒ2(d) = d - rB; CD = ƒ3(d) = d - rC, where d is the radius of ED. In particular, AD = ƒ1(d) = | d - rA|; BD = ƒ2(d) = | d - rB|; CD = ƒ3(d) = | d - rC| > 0, where d is greater than rA, rB, and rC and d is the radius of ED.
In the case that ED is externally tangent to EA, EB, and EC, then AD = ƒ1(d) = rA + d; BD = ƒ2(d) = rB + d; CD = ƒ3(d) = rC + d, where d is the radius of ED. We can rewrite these equations as AD = ƒ1(d) = rA - (-d); BD = ƒ2(d) = rB - (-d); CD = ƒ3(d) = rC - (-d) and again as AD = ƒ1(d) = |(-d) - rA|; BD = ƒ2(d) = |(-d) - rB|; CD = ƒ3(d) = |(-d) - rC|, where (-d) < 0.
Thus in general we have:
- AD = ƒ1(d) = | d - rA|
- BD = ƒ2(d) = | d - rB|
- CD = ƒ3(d) = | d - rC|
where this d ∈ R-{0}. We will see below that in solving for d we get a quadratic in d which yields solutions D1, D2 such that if Di < 0 then | Di| is the radius of an externally tangent ED and if Di > 0 then Di is the radius for ED that surrounds the other three circles.
Now consider the general solution (for both cases A and B) involving the general ƒ1(d), ƒ2(d), ƒ3(d), and then look at the differences when the actual values of these functions are inserted. For ease of notation we will use f = ƒ1, g = ƒ2, h = ƒ3(d). The general problem is to solve the system:
- EA(d): x2 + y2 = f2(d)
- EB(d): (x-c1)2 + (y-c2)2 = g2(d)
- EC(d): (x-b1)2 + y2 = h2(d)
We solve the system in three steps.
- Find the line of intersection for EA(d) and EC(d), LAC(d), as a function of d.
- Find the line of intersection for EA(d) and EB(d), LAB(d), as a function of d.
- Find the points where the lines of intersection intersect our circles of interest, say EA(d).
- The lines of intersection represent the points where the distances to EA(d) and EC(d) or EA(d) and EB(d) are the same for a given d. We want to find d where all three distances are the same for a given d. That is, we want to find the value(s) of d where the lines LAC(d) and LAB(d) intersect. These will give us center points for ED with radius d.
Find LAC(d):
- x2 + y2 - f2(d) = (x-b1)2 + y2 - h2(d)
- x = (b12 + f2 - h2) / 2b1
Find LAB(d):
- x2 + y2 - f2(d) = (x-c1)2 + (y-c2)2 - h2(d)
- 2c1x + 2c2y = c12 + c22 + f2 - g2 = c2 + f2 - g2.
- Letting u = (c2 + f2 - g2) / 2c2, we have y = (-c1/c2)x + u.
Find the intersections with EA(d).
- LAC(d) meets EA(d) at x1(d) = (b12 + f2 - h2) / 2b1 and y1(d) = ±√[f2 - x12(d)].
- LAB(d) meets EA(d) when x2 + ((-c1/c2)x + u)2 = f2.
- This leads to the quadratic equation (c/c2)2x2 - (2c1u/c2)x + u2 -f2 = 0
- Use the quadratic formula to get two solutions for x:
- x2(d) = (c1c2u + c2√[(cf)2 - (d1u)2]) / c2
- x3(d) = (c1c2u - c2√[(cf)2 - (d1u)2]) / c2
- and the corresponding y terms y2(d) = (-c1/c2)x2 + u and y3(d) = (-c1/c2)x3 + u
To find point(s) where all three equations of the system are satisfied we have to find a value(s) for d such that x1(d) = x2(d) or x1(d) = x3(d). That is where
- (b12 + f2 - h2) / 2b1 = (c1c2u ± c2√[(cf)2 - (d1u)2]) / c2
- We isolate the radical, square both sides, substitute for u, and then collect terms with common differences of squares of functions f, g, and h to get:
- (f2 - h2)2[c/b1]2 + (f2 - g2)2 - (f2 - h2)(f2 - g2)[2c1/b1] + (f2 - h2)[2c2(1-c1/b1)] + (f2 - g2)[2(c2 - c1b1)] - 4c22f2 + c2[b12 + c2 - 2c1b1] = 0
Notice that f, g, and h only show up as squares so the absolute value does not come into play when we make the substitutions. By using the values from the beginning of this section we can compute:
- Case A: f2 - g2 = w(2d-c) and f2 - h2 = v(2d-b) where w = -(a + b) and v = -(a + c). Also, f2 = (s-d)2.
- Case B: f2 - g2 = w(2d-c) and f2 - h2 = v(2d-b) where w = (a - b) and v = (a - c). Also, f2 = (d-(s-a))2.
We substitute these values into the equation in the last paragraph and collect terms with the same degree of d to get a quadratic in d: αd2 + βd + κ = 0, where the coefficients for each case are as follows. Recall, b = b1.
-
Case A: w = -(a + b) and v = -(a + c)
- α = 4[(cv/b)2 - 2c1vw/b + w2 - c22]
- β = 4[-(cv)2/b + c1vw(b+c)/b - cw2 + vc2(1-c1/b) + w(c2 - bc1) + 2sc22]
- κ = (cv)2 - 2c1cvw + (cw)2 - 2bvc2(1-c1/b) - 2cw(c2 - bc1) - 4s2c22 + c2[b2 + c2 - 2c1b]
-
Case B: w = (a - b) and v = (a - c)
- α = 4[(cv/b)2 - 2c1vw/b + w2 - c22]
- β = 4[-(cv)2/b + c1vw(b+c)/b - cw2 + vc2(1-c1/b) + w(c2 - bc1) + 2(s-a)c22]
- κ = (cv)2 - 2c1cvw + (cw)2 - 2bvc2(1-c1/b) - 2cw(c2 - bc1) - 4(s-a)2c22 + c2[b2 + c2 - 2c1b]
Notice that besides the values for v and w, the only difference in these cases is the term "s" in Case A is replaced by "s-a" in case B in the β and κ terms. We solve for d = (-β ±√[β2 - 4ακ])/2α. Let D1 be the root with positive radical and let D2 be the root with the negative radical. We interpret the roots as follows.
- Case A: In this case the roots are positive and each gives the radius of one of the two possible 4th tangent circles.
- Case B: If a root is negative, its absolute value is the radius of an externally tangent fourth circle. If a root is positive it is the radius of fourth tangent circle that surrounds the original three.
- In either case, for i = 1, 2 and j = 2, 3: If x1(Di) = xj(Di) then (x - xj(Di))2 + (y - yj(Di))2 = (Di)2 is a fourth tangent circle to the original three.
Examples of four mutually tangent circles
The final part of this article is to show some examples of four tangent circles for different values of b1, c1, and c2. Given the ΔABC we can have the three mutually tangent circles EA, EB, EC with either radii s, s-c, s-b (EA surrounds, case A) or s-a, s-b, s-c (externally tangent, Case B) respectively. We will label our examples below with the notation: [Case,0,0,c1,c2,b1,0] with Case = A or B followed by coordinates of centers A, B, C. For example B,0,0,1,1,1,0 means we are looking at three mutually tangent circles with centers at A(0,0), B(1,1) and C(1,0). In these examples we have included the lines of intersection LAB(d) and LAC(d) for each of the values d = D1 and d = D2. Also, we use the subscript notation D1iji on the D-radii to mean the radius obtained when x1(Di) = xj(Di) for i = 1,2; j = 2,3. The values are given to two decimal places only. Note: Case A 4th tangent circles are shaded purple and Case B circles are shaded red.
-
A,0,0,1,1,1,0
D1222 = 0.14 D(1.37,0.77)
D1131 = 0.71 D(0,1) -
B,0,0,1,1,1,0
D1232 = 1.71 D(0,1)
D1121 = -0.08 D(0.74,0.26) - Notice the dramatic difference with the large surrounding circle at C(2.8,0) and the externally tangent circle at C(2.9,0)
B,0,0,1,1,2.8,0D1222 = 479.71 D(111.57,-465.45)
D1121 = -0.11 D(1.05,0.55) -
B,0,0,1,1,2.9,0
D1232 = -24.00 D(-4.98,24.59)
D1121 = -0.11 D(1.06,0.56) -
A,0,0,1,1,,4.3,0
D1222 = 0.21 D(4.34,0.49)
D1121 = 0.38 D(4.15,-0.65) -
B,0,0,1,1,,4.3,0
D1232 = -2.03 D(0.17,3.16)
D1121 = -0.11 D(1.08,0.62)
No comments:
Post a Comment